Sistem Trigger Database Pada SIAKAD Informatika - Dedianto, Dedianto (Jurusan Informatika Universitas Tanjungpura, 2013)
Tanjungpura University of EngineeringFaculty Pontianak particular use SIAKAD applications in the academic process. ApplicationsSIAKAD facilitate students to perform academicprocess as a process of inputting LIRS, LIHS,transcript Value and others. This application is to helpstudents because the students no longer bothered towrite all the subjects as in the old system but simplyby selecting options from the application. The systemwas developed to complement SIAKAD application isto use the trigger. Trigger serves as the commandfunction of data duplication. Any data that is enteredeither by students or faculty the trigger will make abackup copy of the database. Trigger requires asystem to be able to access the database residing on adifferent server by using Federated Storage Engine. Federated Storage Engine to be a bridge that connectsto the database backup trigger. Each event occursInsert, Update and Delete the backup database triggerwill access through the Federated Storage Engineexecutes the same event on the backupdatabase.Trigger tested with black-box method, thetest results when doing Insert, Update and Delete thetrigger is executed and the process the same on thebackup database.